Studies on Antibacterial Activity and Brine Shrimp Toxicity of Leaf Extract of Cassia grandis (Bangladesh Journal of Medical Microbiology, 2009)
Antibacterial activity and toxicity of ethanol extract of Cassia grandis leaves to Brine Shrimp was evaluated. Five Gram-positive and 4 Gram-negative bacteria, namely Sarcina lutea, Bacillus megaterium, Bacillus subtilis, Streptococcus ß-haemolyticus, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Salmonella typhi and Klebsiella pneumoniae were tested using disc diffusion method. The extract was inactive at the concentration of 30 μg/disc but exhibited moderate to good activity at concentration of 200 μg/disc against the tested bacteria. In Brine Bhrimp lethality bioassay test, it was observed that LC50 value of the extract was 10.68 μg/ml. From these findings, it is indicative that C. grandis may be useful against microbial diseases. Key words: Antibacterial activity, Brine shrimp, Cassia grandis   doi: 10.3329/bjmm.v3i1.2966 Bangladesh J Med Microbiol 2009; 03 (01): 17-19